Self-Compassion Levels Among Guidance and Counseling Students: A Descriptive Quantitative Study - Siddik, Riesa; Nurihsan, Juntika; Budiman, Nandang; Saripah, Ipah (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
This study aimed to examine the distribution of university students’ levels of self-compassion based on its psychological aspects. The research employed a descriptive quantitative approach involving 144 students from guidance and counseling study program at a higher education institution. The entire population was included as reasearch participants without applying any sampling technique. Data were collected using a self compassion scale developed in the form of a likert model, which encompasses six core dimensions: self-kindness, self-judgment, common humanity, isolation, mindfulness and over=identification. Data analysis was conducted using descriptive percentage techniques to classify self-compassion levels into three categories, namely low, moderate, and high. The results indicated that, everall, most students were classified in the moderate level of self-compassion (48%), followed by those in the low category (0%) and the high category (52%). Further analysis of each dimension showed that the majority of students also fell into the moderate category, with percentage distributions exceeding 40% across all aspects. These findings suggest that studentsself commpassion has not yet developed optimally and tends to remain at a moderate level. This condition indicates the need for systematic developmental efforts oriented toward strengthening students’ psychological aspects, particularly in fostering adative self-attitudes, emotional awarness, and balanced self-evaluation. The results of this study can serve as an empirical basis for designing guidance and counseling programs aimed at enhancing self-compassion among university students.